Research note: examining the connection of organizational citizenship behaviors with supervisor and management trust among correctional staff - Lambert, Eric (Criminal justice studies, 2024)
Organizational citizenship behaviors (OCBs) refer to going above and beyond what is expected at work; they are important for the improved functioning of many organizations, including institutional corrections. Trust in supervisors and trust in management may be related to institutional correctional staff engaging in OCBs. The current study examined these associations among staff at a U.S. high-security closed facility. Ordinary Least Squares regression indicated that supervisor trust had a significant association with OCBs, but management trust did not. Based on the results, feedback from staff and more research is needed on how to build supervisor trust among staff.